2017
DOI: 10.7567/apex.10.087201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin epidermal strain sensor based on an elastomer nanosheet with an inkjet-printed conductive polymer

Abstract: To minimize the interference that skin-contact strain sensors cause natural skin deformation, physical conformability to the epidermal structure is critical. Here, we developed an ultrathin strain sensor made from poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) inkjet-printed on a polystyrene–polybutadiene–polystyrene (SBS) nanosheet. The sensor, whose total thickness and gauge factor were ∼1 µm and 0.73 ± 0.10, respectively, deeply conformed to the epidermal structure and successfully det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
(27 reference statements)
0
33
0
Order By: Relevance
“…We previously investigated the mechanical and electrical stability of the PEDOT:PSS-based conductive nanosheets against sweat and found that they retained their proper electrical functions with structural integrity against immersion in artificial sweat solutions at pH 5.5 and pH 8.0 for at least 180 min 31 . In addition, our group demonstrated that bilayered elastic conductive nanosheets consisting of PEDOT:PSS and polystyrene-polybutadiene-polystyrene triblock copolymer (SBS) conformably adhered to human skin without any adhesive reagents and that they did not interfere with the natural deformation of skin because they have low flexural rigidity (<10 -2 nN m) 33 . In this study, we prepared a PEDOT:PSS/SBS bilayered conductive nanosheet with a thickness of 339 ± 91 nm (PEDOT:PSS layer:~168 nm, SBS layer:~171 nm), a conductivity of~500 S/cm, and a flexural rigidity of less than 10 -2 nN m (Fig.…”
Section: Preparation Of Conductive Nanosheets and Attachment To The Smentioning
confidence: 99%
See 1 more Smart Citation
“…We previously investigated the mechanical and electrical stability of the PEDOT:PSS-based conductive nanosheets against sweat and found that they retained their proper electrical functions with structural integrity against immersion in artificial sweat solutions at pH 5.5 and pH 8.0 for at least 180 min 31 . In addition, our group demonstrated that bilayered elastic conductive nanosheets consisting of PEDOT:PSS and polystyrene-polybutadiene-polystyrene triblock copolymer (SBS) conformably adhered to human skin without any adhesive reagents and that they did not interfere with the natural deformation of skin because they have low flexural rigidity (<10 -2 nN m) 33 . In this study, we prepared a PEDOT:PSS/SBS bilayered conductive nanosheet with a thickness of 339 ± 91 nm (PEDOT:PSS layer:~168 nm, SBS layer:~171 nm), a conductivity of~500 S/cm, and a flexural rigidity of less than 10 -2 nN m (Fig.…”
Section: Preparation Of Conductive Nanosheets and Attachment To The Smentioning
confidence: 99%
“…6 MPa, flexural rigidity:~10 -5 nN m), stretchability (elongation:~150%), and robustness (maximum tensile strength:~1.0 MPa) of the SBS nanosheet 33,34 enabled the bilayered PEDOT:PSS/SBS conductive nanosheet to conform to van-der-Waals-force-based conformable adhesion to the skin without the use of any adhesive agents.…”
Section: Preparation Of Conductive Nanosheets and Attachment To The Smentioning
confidence: 99%
“…[1] Various thin-film biosensors, [2] cardiac sensors, [3] and stimulators [4] are conformable to biological tissues and soft materials because of low flexural rigidity. [22] In addition, conductive polymer inks were printed on nanosheets made from poly(styrene-block-butadiene-block-styrene) and PLA for engineering a strain gauge sensor to measure the deformation of human skin with less movement interference, [23] and for a neural probe having similar mechanical properties to brain tissue. Elastomeric nanosheets made from silicone have been also prepared for implanting electrical devices such as IC chips and LEDs in a body.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a nanosheet can be used as a substrate of a wearable device. 1,[14][15][16][17][18][19][20] It is considered that the adhesion energy of a nanosheet to the skin is related to conformability to epidermal depressions. Nevertheless, the relationship between conformability to the human skin and the adhesion energy has not yet been measured.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] When the film thickness is several µm or more, glue or an adhesive layer such as gel or silicone is needed to attach onto the human skin. [2][3][4][5][6][7][8][9][10][11][12][13] On the contrary, a nanosheet with thickness of hundreds of nanometers is thin and flexible, therefore, it conforms to the surface shape of the object such as epidermal depressions and can be attached by just placing the wet nanosheet on the object without glue or adhesive layer.…”
Section: Introductionmentioning
confidence: 99%